Cognitive and behavioural treatments of primary insomnia: A review - Malaffo, M; Espie, C (2007)
Despite insomnia affecting around 15% of the adult population and being associated with personal and socio-economic costs, it remains inadequately treated. When patients report insomnia to their primary physician, pharmacotherapy is typically the treatment choice offered despite recent guidelines (NIH and NICE) stating that hypnotic drugs should be used only short-term in the management of transient insomnia, while nonpharmacological therapies should be the treatment choice in persistent insomnia. Indeed, in the last thirty-five years research of cognitive and behavioural therapies for insomnia has provided ample evidence of their efficacy in ameliorating sleep difficulties. More recentiy, randomised controlled clinical trials have lent support to the use of cognitive-behavioural therapy (CBT-I) to treat primary insomnia and insomnia associated to other disorders in primary care settings. The aim of this paper is to briefly explain cognitive and behavioural treatments for insomnia and to review empirically supported literature on insomnia. Overall, it was concluded that cognitive behavioural treatment of insomnia has shown strong success in the management of insomnia both in the short- and long-terms. Recent trials suggest promising areas for future inquiry such as the feasibility of employing health professionals (e.g. nurses and health visitors) to deliver manualised CBT-I, employing CBT-I to help discontinuing hypnotic drug use, investigating the optimal dose of CBT-I to achieve target outcomes (dose-response curve analyses), assessing the effectiveness of very brief interventions and the efficacy of CBT-I when insomnia is associated to other disorders.